Colombian coffee (Coffea arabica L.) plantations: a taxonomic and functional survey of soil fungi - Ochoa-Henriquez, Victor Hugo; Faggioli, Valeria; Gómez-Godínez, Lorena Jacqueline; Rivarola, Maximo; Cristancho, Marco (Frontiers in Sustainable Food Systems, 2024)
Fungi are essential players in the maintenance of global coffee productivity, but their taxonomic and functional diversity in tropical and subtropical soils of Latin America remains largely unexplored. To address this concern, soil fungi were surveyed in six farms in three traditional coffee-growing regions of Colombia (Cauca, Magdalena, and Risaralda). Five farms were organic and newly established (<1 to 15 years) with low shade, and one farm was under long-term conventional management (>30 years old) with higher shade cover. We used amplicon sequencing and functional prediction based on the FUNGuild annotation tool. Fungal community composition diverged among farms, with Mortierella (Mortierellomycota) and Saitozyma (Basidiomycota) among the most prevalent genera. Functional prediction revealed the predominance of saprotroph-symbiotroph and pathotroph fungi. The endophyte and litter decomposer Mortierella genus was dominant within the saprotrophs and symbiotrophs. The pathotroph community was characterised by insect pathogen species belonging to the Metarhizium (Ascomycota) genus. Indeed, M. anisopliae and M. marquandii were identified as indicator species in the conventional long-term shaded farm. This study revealed that coffee plantations sustain a diverse fungal community and nurture potentially beneficial species. Further studies are needed to elucidate how particular management practices can nourish beneficial fungi, suppress detrimental species, and promote more sustainable coffee production.